2014
DOI: 10.18632/oncotarget.2821
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylome analysis identifies epigenetic silencing of FHIT as a determining factor for radiosensitivity in oral cancer: an outcome-predicting and treatment-implicating study

Abstract: Radioresistance is still an emerging problem for radiotherapy of oral cancer. Aberrant epigenetic alterations play an important role in cancer development, yet the role of such alterations in radioresistance of oral cancer is not fully explored. Using a methylation microarray, we identified promoter hypermethylation of FHIT (fragile histidine triad) in radioresistant OML1-R cells, established from hypo-fractionated irradiation of parental OML1 radiosensitive oral cancer cells. Further analysis confirmed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 72 publications
1
33
0
Order By: Relevance
“…Further support for the role of FHIT in the DDR comes from DNA methylome analysis showing that epigenetic silencing of FHIT as a determining factor for radiosensitivity in oral cancer [77]. Ectopic expression of FHIT inhibited tumor growth in both in vitro and in vivo models and resensitized radioresistant cancer cells to irradiation by restoring Chk2 phosphorylation and G2/M arrest [77].…”
Section: Cfs Gene Products With Roles In the Ddrmentioning
confidence: 99%
See 1 more Smart Citation
“…Further support for the role of FHIT in the DDR comes from DNA methylome analysis showing that epigenetic silencing of FHIT as a determining factor for radiosensitivity in oral cancer [77]. Ectopic expression of FHIT inhibited tumor growth in both in vitro and in vivo models and resensitized radioresistant cancer cells to irradiation by restoring Chk2 phosphorylation and G2/M arrest [77].…”
Section: Cfs Gene Products With Roles In the Ddrmentioning
confidence: 99%
“…Ectopic expression of FHIT inhibited tumor growth in both in vitro and in vivo models and resensitized radioresistant cancer cells to irradiation by restoring Chk2 phosphorylation and G2/M arrest [77]. …”
Section: Cfs Gene Products With Roles In the Ddrmentioning
confidence: 99%
“…Recently, a study found that high expression of MUC13 was associated with deceased expression of tumor suppressor, p53, and also the activation or expression of crucial oncogenes, HER2, PAK1, ERK, Akt, and S100A4 [16]. Another study demonstrated that miR-145 can suppress tumor growth of pancreatic cancer through its inhibitory effects on MUC13 [31]. These implied that MUC13 might become an effective therapeutic target for cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Fragile histidine triad ( FHIT ) gene regulates G2/M checkpoint and is located in a fragile chromosome site (3p13.2), which would likely be damaged by ionizing irradiation, Lin et al6 selected it for study. In oral carcinoma cell lines, the promoter of FHIT gene was hyper‐methylated in radio‐resistant cells.…”
Section: Radio‐sensitivity and Dna Methylation Of Cell Cycle‐related mentioning
confidence: 99%
“…However, parts of patients with above tumors are resistant to irradiation or some initially sensitive patients develop into irradiation resistance. Hence, irradiation resistance is 1 of the major obstacles that leads to loco‐regional recurrence of malignant tumors during treatment 2, 3, 4, 5, 6…”
Section: Introductionmentioning
confidence: 99%